A method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel block

By introducing Cu-MOF powder into the ceramic bonding agent diamond grinding wheel, Cu-MOF modified ceramic bonding agent diamond grinding wheel block is solved, and the problem of high porosity leads to reduced strength is achieved, and higher flexural strength and better Long service life.

CN118005420BActive Publication Date: 2025-02-11HANGZHOU XINYANKE SEMICON MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410170413.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2025-02-11
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

The existing ceramic bonding agent diamond grinding wheel has a high porosity, resulting in a reduced strength, making it difficult to meet the high requirements of ultra-precision grinding technology for grinding wheel performance.

Method used

Cu-MOF modified ceramic binder is used to mix Cu-MOF powder with base ceramic binder, pore-forming agent, diamond particles and adhesive, and molding and sintering treatment to form Cu-MOF modified Ceramic bonding agent diamond grinding wheel block.

Benefits of technology

While increasing the porosity of the grinding wheel, the flexural strength of the grinding wheel and the strength of the bonding agent are enhanced, and the performance and life of the grinding wheel are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118005420B_ABST
    Figure CN118005420B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel block, belonging to the technical field of diamond grinding wheel preparation. The present invention first grinds, melts, quenches and dries silicon dioxide, boron trioxide, aluminum oxide and sodium oxide in sequence to obtain a basic ceramic bond; isonicotinic acid and copper acetate monohydrate are mixed and ball milled to obtain Cu-MOF powder; finally, the basic ceramic bond, pore-forming agent, Cu-MOF powder, diamond particles and adhesive are mixed and molded and sintered in sequence to obtain a Cu-MOF modified ceramic bond diamond grinding wheel block. The Cu-MOF powder in the present invention generates a large amount of gas during sintering, forming some small micropores, which are distributed in the grinding wheel block, and copper atoms are oxidized into extremely fine copper oxide particles, which can strengthen the strength of the ceramic bond, thereby improving the performance of the grinding wheel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diamond grinding wheel preparation, and in particular to a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel block. Background Art

[0002] Vitrified bond diamond grinding wheels are widely used for high-precision grinding of hard and brittle materials, such as grinding polycrystalline diamond blades, semiconductor substrates, cemented carbides, and new ceramics. Compared with metal or resin bond diamond grinding wheels, vitrified bond diamond grinding wheels have attracted much attention due to their good shape retention, excellent self-dressing ability, and good load-bearing capacity.

[0003] The vitrified bond diamond grinding wheel is composed of a grinding wheel block and a matrix. The grinding wheel block is the component of the grinding wheel that plays a grinding role. The grinding wheel block is made by sintering diamond abrasives and auxiliary abrasives at a certain temperature with a vitrified bond as a binder. The typical structure of the grinding wheel block is composed of diamond abrasives, a binder, an auxiliary abrasive and pores. The pores are an indispensable component of the grinding wheel block. They play the role of chip storage and chip removal during grinding, thereby effectively improving the grinding efficiency. At the same time, the grinding wheel has a good heat dissipation effect, thereby reducing the heat generated by grinding. In actual production, it is necessary to introduce a pore-forming agent into the grinding wheel to adjust the porosity. The more common pore-forming agents are walnut shell debris, charcoal, coke, resin powder, organic plastic balls, hollow alumina balls, etc. The pore-forming agent is introduced into the grinding wheel to play a role in regulating the number, size and distribution of pores, thereby effectively improving the performance of the grinding wheel.

[0004] With the development of modern ultra-precision grinding technology, the requirements for ceramic bond diamond grinding wheels are getting higher and higher. The particle size of diamond and bond used in ultra-precision grinding wheels is getting finer and finer, and the grinding wheel is required to have better chip holding and chip removal capabilities, so the higher the porosity, the better. However, increasing the porosity will inevitably weaken the holding force of the bond on the diamond. On a macro scale, the overall strength of the grinding wheel will be significantly reduced, which will inevitably reduce the performance and life of the grinding wheel. For example, when grinding single-crystal silicon wafers, the geometric accuracy of the wafer may not meet the index requirements, or the grinding wheel may be consumed too quickly and have a short service life. Therefore, it is of great significance to study a method for preparing a Cu-MOF-modified ceramic bond diamond grinding wheel block to improve the porosity and strength of the diamond grinding wheel block. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel block, so as to solve the problem in the prior art that the diamond grinding wheel has a high porosity but may lead to reduced strength.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel segment, comprising the following steps:

[0008] (1) mixing silicon dioxide, boron trioxide, aluminum oxide and sodium oxide, grinding, smelting, rapid cooling and drying in sequence to obtain a basic ceramic binder;

[0009] (2) mixing isonicotinic acid and copper acetate monohydrate and then ball milling to obtain Cu-MOF powder;

[0010] (3) The base ceramic binder, pore-forming agent, Cu-MOF powder, diamond particles and adhesive are mixed and then molded and sintered in sequence to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0011] Preferably, in step (1), the mass ratio of silicon dioxide, boron trioxide, aluminum oxide and sodium oxide is 50-70:10-15:5-10:15-22.

[0012] Preferably, in step (1), the smelting temperature is 1200-1300° C., and the smelting time is 2-4 hours.

[0013] Preferably, in step (1), the drying temperature is 80 to 120° C., and the drying time is 6 to 12 hours.

[0014] Preferably, in step (2), the mass ratio of isonicotinic acid to cupric acetate monohydrate is 2 to 3:1.

[0015] Preferably, in step (2), the ball-to-material ratio of the ball milling treatment is 10 to 20:1, the rotation speed of the ball milling treatment is 500 to 600 rpm, and the ball milling treatment time is 2 to 4 hours.

[0016] Preferably, in step (3), the mass ratio of the basic ceramic binder, the pore former, the Cu-MOF powder, the diamond particles and the adhesive is 24-40:12-30:6-20:50-70:3-9; the D50 of the diamond particles is 1-70 μm; and the pore former is polymethyl methacrylate microspheres.

[0017] Preferably, in step (3), the pressure of the molding process is 4 to 6 MPa, and the time of the molding process is 5 to 15 s.

[0018] Preferably, in step (3), the sintering treatment includes a first-stage sintering treatment and a second-stage sintering treatment, the temperature of the first-stage sintering treatment is 300-400°C, the time of the first-stage sintering treatment is 1-3 hours, the temperature of the second-stage sintering treatment is 700-800°C, and the time of the second-stage sintering treatment is 1-3 hours.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention adds Cu-MOF powder when preparing the ceramic bond diamond grinding wheel block. During the sintering process of the grinding wheel block, the Cu-MOF powder generates a large amount of gas, which can form some small micropores and disperse in the grinding wheel structure, which has the function of assisting pore formation and is a very beneficial supplement to the traditional pore forming agent. In addition, the copper atoms are oxidized into extremely fine copper oxide particles, which are combined with the basic ceramic bond to strengthen the strength of the ceramic bond, thereby improving the performance of the grinding wheel.

[0021] (2) The grinding wheel block prepared by the present invention has high flexural strength, the basic ceramic binder has good wetting and adhesion to diamond, and has good holding power. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD pattern of the product obtained by thermally decomposing the Cu-MOF powder prepared in Example 1 at 350°C and then calcining at 720°C;

[0023] Figure 2 This is a SEM image of the product obtained by thermally decomposing the Cu-MOF powder prepared in Example 1 at 350°C and then calcining at 720°C;

[0024] Figure 3 This is a SEM image of the vitrified bond diamond grinding wheel block prepared in Comparative Example 1;

[0025] Figure 4 This is a SEM image of the Cu-MOF modified ceramic bond diamond grinding wheel segment prepared in Example 1;

[0026] Figure 5 The SEM images of the ceramic bond diamond grinding wheel block prepared in Comparative Example 2, a is a SEM image magnified 200 times, and b is a SEM image magnified 1600 times;

[0027] Figure 6 The SEM images of the Cu-MOF modified ceramic bond diamond grinding wheel block prepared in Example 2, a is a SEM image magnified 200 times, and b is a SEM image magnified 1600 times;

[0028] Figure 7 This is a SEM image of the vitrified bond diamond grinding wheel block prepared in Comparative Example 3;

[0029] Figure 8 This is a SEM image of the Cu-MOF modified ceramic bond diamond grinding wheel segment prepared in Example 3;

[0030] Fig. 9 This is a SEM image of the vitrified bond diamond grinding wheel block prepared in Comparative Example 4;

[0031] Fig.10 This is the SEM image of the Cu-MOF modified ceramic bond diamond grinding wheel segment prepared in Example 4. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel segment, comprising the following steps:

[0033] (1) mixing silicon dioxide, boron trioxide, aluminum oxide and sodium oxide, grinding, smelting, rapid cooling and drying in sequence to obtain a basic ceramic binder;

[0034] (2) mixing isonicotinic acid and copper acetate monohydrate and then ball milling to obtain Cu-MOF powder;

[0035] (3) The base ceramic binder, pore-forming agent, Cu-MOF powder, diamond particles and adhesive are mixed and then molded and sintered in sequence to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0036] In the present invention, in the step (1), the mass ratio of silicon dioxide, boron trioxide, aluminum oxide and sodium oxide is 50-70:10-15:5-10:15-22, preferably 55-65:11-14:6-9:18-21, and more preferably 60:13:7-8:19-20.

[0037] In the present invention, silicon dioxide, boron trioxide, aluminum oxide and sodium oxide are ground and preferably passed through a 100-200 mesh sieve, and then smelted.

[0038] In the present invention, in the step (1), the smelting temperature is 1200-1300°C, preferably 1220-1280°C, more preferably 1250°C, and the smelting time is 2-4h, preferably 2.5-3.5h, more preferably 3h.

[0039] In the present invention, in the step (1), it is preferred that after smelting, the glass material is rapidly cooled with tap water at room temperature to obtain the glass material, and the glass material is taken out of the water and then dried.

[0040] In the present invention, in step (1), the drying temperature is 80 to 120° C., preferably 90 to 110° C., more preferably 100° C., and the drying time is 6 to 12 h, preferably 7 to 11 h, more preferably 8 to 10 h.

[0041] In the present invention, in the step (1), the dried product is preferably ground and passed through a 200-300 mesh sieve to obtain a basic ceramic binder.

[0042] In the present invention, in the step (2), the mass ratio of isonicotinic acid to cupric acetate monohydrate is 2 to 3:1, preferably 2.2 to 2.8:1, and more preferably 2.4 to 2.6:1.

[0043] In the present invention, the ball milling medium of the ball milling treatment is preferably a tungsten carbide grinding ball with a diameter of 10 mm; before the ball milling treatment, preferably 2 to 5 drops of deionized water are dripped into the ball milling jar before the ball milling treatment is performed.

[0044] In the present invention, in step (2), the ball-to-material ratio of the ball milling treatment is 10 to 20:1, preferably 12 to 18:1, and more preferably 15:1; the rotation speed of the ball milling treatment is 500 to 600 rpm, preferably 520 to 580 rpm, and more preferably 550 rpm; the ball milling treatment time is 2 to 4 hours, and more preferably 3 hours.

[0045] In the present invention, the ball-milled product is preferably washed three times with deionized water and then dried to obtain Cu-MOF powder.

[0046] In the present invention, in the step (3), the mass ratio of the basic ceramic binder, the pore-forming agent, the Cu-MOF powder, the diamond particles and the adhesive is 24-40:12-30:6-20:50-70:3-9, preferably 25-35:13-17:7-11:55-66:4-8, and more preferably 27-30:14-16:8-10:58-63:6-7; the D50 of the diamond particles is 1-70 μm, preferably 5-40 μm, and more preferably 10-30 μm; the pore-forming agent is polymethyl methacrylate microspheres, and the particle size of the polymethyl methacrylate microspheres is 200 / 325#, and 200 / 325# means that the particle size is between 200 and 325 meshes.

[0047] In the present invention, there is no particular limitation on the type of the adhesive, and any adhesive with an adhesive function that can be obtained by a person skilled in the art can be used as the adhesive. In the present invention, paraffin wax is preferably used as the adhesive.

[0048] In the present invention, the basic ceramic binder, pore-forming agent, Cu-MOF powder, diamond particles and adhesive are preferably mixed uniformly before adding the adhesive. After adding the adhesive, it is preferably heated, ground and sieved in sequence to obtain a molding material, and the obtained molding material is then subjected to molding treatment.

[0049] In the present invention, in the step (3), the pressure of the molding treatment is 4 to 6 MPa, preferably 5 MPa, and the time of the molding treatment is 5 to 15 s, preferably 8 to 12 s, and more preferably 10 s.

[0050] In the present invention, in the step (3), the sintering treatment includes a first stage sintering treatment and a second stage sintering treatment, the temperature of the first stage sintering treatment is 300-400°C, preferably 320-380°C, and more preferably 350°C, the time of the first stage sintering treatment is 1-3h, and more preferably 2h, the temperature of the second stage sintering treatment is 700-800°C, preferably 710-780°C, and more preferably 720-760°C, and the time of the second stage sintering treatment is 1-3h, and more preferably 2h.

[0051] During the sintering process, the Cu-MOF powder undergoes a decomposition reaction (reaction formula (1)). The generated copper ions react with oxygen in the air to form copper oxide particles (see Figure 1 ), the copper oxide particles are very small, with a particle size of 50 to 500 nm (see Figure 2 ), and remain in the Cu-MOF modified ceramic bond diamond grinding wheel block. At the same time, the C atoms and H atoms in MOF react with oxygen to generate CO2 and H2O, which exist in the form of gas and leave pores in the grinding wheel block. Therefore, adding Cu-MOF powder to the grinding wheel block not only plays a role in assisting pore formation, but also uses fine copper oxide particles to increase the strength of the grinding wheel.

[0052] C 18 H 12 Cu3O 15 +15O2=3CuO+18CO2+6H2O (1)

[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] Silicon dioxide, boron trioxide, aluminum oxide and sodium oxide are mixed in a mass ratio of 60:13:7:20 and ground, and passed through a 200-mesh sieve to obtain a mixture, which is placed in a high-temperature furnace, heated to 1200°C at a heating rate of 3°C / min, kept at 1200°C for 4 hours, and then quenched with normal temperature tap water to obtain glass material, which is taken out of the water and dried at 100°C for 10 hours, then ground again after drying, and passed through a 200-mesh sieve to obtain a basic ceramic binder.

[0056] 24.6 g of isonicotinic acid and 10 g of copper acetate monohydrate were placed in a high-energy planetary ball mill. Two drops of deionized water were dripped into the ball mill jar. Tungsten carbide grinding balls (diameter of 10 mm, ball-to-material ratio of 10:1) were added and ball milled at a speed of 550 rpm for 3 h. The ball-milled product was washed 4 times with deionized water and 3 times with anhydrous ethanol, and finally placed in a blast drying oven at 80 °C for 5 h. Finally, it was ground and passed through a 300-mesh sieve to obtain Cu-MOF powder.

[0057] 10g basic ceramic binder, 4.8g polymethyl methacrylate microspheres (particle size 200 / 325#), 20g diamond particles (D50 is 10μm), and 3.2g Cu-MOF powder were placed in a mortar for grinding, and then passed through a 150-mesh sieve three times after grinding. Then, 2g paraffin was added and stirred evenly, and then heated to 80°C for 60min, ground evenly and passed through a 60-mesh sieve three times to obtain a molding material; the molding material was loaded into a mold, and a cold press (model: MY-30) was used to maintain a pressure of 5MPa for 10s to obtain a 50mm×8mm×8mm rectangular blank; the rectangular blank was placed in a high-temperature furnace, heated to 350°C at a heating rate of 5°C / min and kept warm for 2h, and then heated to 720°C at a heating rate of 5°C / min and kept warm for 2h to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0058] from Figure 1 It can be seen that after the decomposition of Cu-MOF powder, sub-μm copper oxide products were obtained, which can improve the strength of the grinding wheel block.

[0059] Example 2

[0060] Silicon dioxide, boron trioxide, aluminum oxide and sodium oxide were mixed in a mass ratio of 70:15:10:22 and ground, and passed through a 100-mesh sieve to obtain a mixture, which was placed in a high-temperature furnace, heated to 1250°C at a heating rate of 3°C / min, kept at 1250°C for 3 hours, and then quenched with normal temperature tap water to obtain glass material, which was taken out of the water and dried at 80°C for 12 hours, then ground again after drying, and passed through a 230-mesh sieve to obtain a basic ceramic binder.

[0061] 20g of isonicotinic acid and 10g of copper acetate monohydrate were placed in a high-energy planetary ball mill. Three drops of deionized water were dripped into the ball mill jar. Tungsten carbide grinding balls (diameter of 10mm, ball-to-material ratio of 15:1) were added and ball milled at a speed of 550rpm for 2h. The ball-milled product was washed with deionized water 4 times and anhydrous ethanol 3 times in sequence, and finally placed in a blast drying oven at 80°C for 5h. Finally, it was ground and passed through a 300-mesh sieve to obtain Cu-MOF powder.

[0062] 11.2g basic ceramic binder, 4.4g polymethyl methacrylate microspheres (particle size 200 / 325#), 18.4g diamond particles (D50 is 5μm), and 3.6g Cu-MOF powder were placed in a mortar for grinding, and then passed through a 150-mesh sieve three times after grinding. Then, 2.4g paraffin was added and stirred evenly, and then heated to 80°C and kept warm for 60min, and ground evenly and passed through a 60-mesh sieve three times to obtain a molding material; the molding material was loaded into a mold, and a cold press (model: MY-30) was used to maintain a pressure of 5MPa for 10s to obtain a 50mm×8mm×8mm rectangular blank; the rectangular blank was placed in a high-temperature furnace, heated to 380°C at a heating rate of 5°C / min and kept warm for 2h, and then heated to 750°C at a heating rate of 5°C / min and kept warm for 2h to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0063] Example 3

[0064] Silicon dioxide, boron trioxide, aluminum oxide and sodium oxide were mixed in a mass ratio of 50:10:5:15 and ground, and passed through a 150-mesh sieve to obtain a mixture, which was placed in a high-temperature furnace, heated to 1300°C at a heating rate of 3°C / min, kept at 1300°C for 2 hours, and then quenched with normal temperature tap water to obtain glass material, which was taken out of the water and dried at 120°C for 6 hours, then ground again after drying, and passed through a 200-mesh sieve to obtain a basic ceramic binder.

[0065] 30g of isonicotinic acid and 10g of copper acetate monohydrate were placed in a high-energy planetary ball mill. Four drops of deionized water were dripped into the ball mill jar. Tungsten carbide grinding balls (diameter of 10mm, ball-to-material ratio of 10:1) were added and ball milled at a speed of 500rpm for 4h. The ball-milled product was washed with deionized water 4 times and anhydrous ethanol 3 times in sequence, and finally placed in a blast drying oven at 80°C for 5h. Finally, it was ground and passed through a 300-mesh sieve to obtain Cu-MOF powder.

[0066] 9.2g of basic ceramic binder, 5.2g of polymethyl methacrylate microspheres (particle size 200 / 325#), 20.8g of diamond particles (D50 is 30μm), and 2.8g of Cu-MOF powder were placed in a mortar for grinding, and then passed through a 150-mesh sieve for 3 times after grinding. Then, 2g of paraffin was added and stirred evenly, and the mixture was heated to 80°C and kept warm for 60min, and then ground evenly and passed through a 60-mesh sieve for 3 times to obtain a molding material; the molding material was loaded into a mold, and a cold press (model: MY-30) was used to maintain a pressure of 5MPa for 10s to obtain a 50mm×8mm×8mm rectangular blank; the rectangular blank was placed in a high-temperature furnace, heated to 400°C at a heating rate of 5°C / min and kept warm for 1h, and then heated to 700°C at a heating rate of 5°C / min and kept warm for 3h to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0067] Six Cu-MOF modified ceramic bond diamond grinding wheel segments were prepared according to the preparation process of Example 3, and a flexural strength test was carried out. The average value of the six test results was taken. The result was: the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment was 53.1 MPa, which was 23.8% higher than the flexural strength of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 3.

[0068] Example 4

[0069] Silicon dioxide, boron trioxide, aluminum oxide and sodium oxide were mixed in a mass ratio of 60:13:8:18 and ground, and passed through a 180-mesh sieve to obtain a mixture, which was placed in a high-temperature furnace, heated to 1300°C at a heating rate of 3°C / min, kept at 1300°C for 3 hours, and then quenched with normal temperature tap water to obtain glass material, which was taken out of the water and dried at 110°C for 8 hours, then ground again after drying, and passed through a 230-mesh sieve to obtain a basic ceramic binder.

[0070] 28 g of isonicotinic acid and 10 g of copper acetate monohydrate were placed in a high-energy planetary ball mill. Five drops of deionized water were dripped into the ball mill jar. Tungsten carbide grinding balls (diameter of 10 mm, ball-to-material ratio of 10:1) were added and ball milled at a speed of 600 rpm for 2 h. The ball-milled product was washed 4 times with deionized water and 3 times with anhydrous ethanol in sequence, and finally placed in a blast drying oven at 80 °C for 5 h. Finally, it was ground and passed through a 300-mesh sieve to obtain Cu-MOF powder.

[0071] 8.4g basic ceramic binder, 5.6g polymethyl methacrylate microspheres (particle size 200 / 325#), 22g diamond particles (D50 is 70μm), and 2.4g Cu-MOF powder were placed in a mortar for grinding, and then passed through a 150-mesh sieve for 3 times after grinding. Then, 1.6g paraffin was added and stirred evenly, and then heated to 80°C and kept warm for 60min. After grinding evenly, it was passed through a 60-mesh sieve for 3 times to obtain a molding material; the molding material was loaded into a mold, and a cold press (model: MY-30) was used to maintain a pressure of 5MPa for 10s to obtain a 50mm×8mm×8mm rectangular blank; the rectangular blank was placed in a high-temperature furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 3h, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 1h to obtain a Cu-MOF modified ceramic binder diamond grinding wheel block.

[0072] Six Cu-MOF modified ceramic bond diamond grinding wheel segments were prepared according to the preparation process of Example 4, and a flexural strength test was carried out. The average value of the six test results was taken. The result was: the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment was 59.8 MPa, which was 19.4% higher than the flexural strength of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 4.

[0073] Comparative Example 1

[0074] The difference from Example 1 is that no Cu-MOF powder is added, the addition amount of polymethyl methacrylate microspheres (particle size is 200 / 325#) is 8 g, and other conditions are the same to obtain a ceramic bond diamond grinding wheel block.

[0075] Comparative Example 2

[0076] The difference from Example 2 is that no Cu-MOF powder is added, the addition amount of polymethyl methacrylate microspheres (particle size is 200 / 325#) is 8 g, and other conditions are the same to obtain a ceramic bond diamond grinding wheel block.

[0077] Comparative Example 3

[0078] The difference from Example 3 is that no Cu-MOF powder is added, the addition amount of polymethyl methacrylate microspheres (particle size is 200 / 325#) is 8 g, and other conditions are the same to obtain a ceramic bond diamond grinding wheel block.

[0079] Comparative Example 4

[0080] The difference from Example 4 is that no Cu-MOF powder is added, the addition amount of polymethyl methacrylate microspheres (particle size is 200 / 325#) is 8 g, and other conditions are the same to obtain a ceramic bond diamond grinding wheel block.

[0081] According to the preparation process of Examples 1 to 4 and Comparative Examples 1 to 4, 6 ceramic bond diamond grinding wheel segments were prepared for each Example and Comparative Example, and the flexural strength test was carried out. The average value of the 6 test results was taken, and the results were as follows: the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 1 was 47.9 MPa, and the flexural strength of the ceramic bond diamond grinding wheel segment of Comparative Example 1 was 40.2 MPa. The flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 1 was 19.2% higher than that of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 1; the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 2 was 45.1 MPa, and the flexural strength of the ceramic bond diamond grinding wheel segment of Comparative Example 2 was 38.7 MPa. The flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 2 was 44.8 MPa. Compared with the flexural strength of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 2, it is increased by 16.5%; the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 3 is 53.1MPa, and the flexural strength of the ceramic bond diamond grinding wheel segment of Comparative Example 3 is 42.9MPa. The flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 3 is increased by 23.8% compared with the flexural strength of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 3; the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 4 is 59.8MPa, and the flexural strength of the ceramic bond diamond grinding wheel segment of Comparative Example 4 is 50.1MPa. Compared with the flexural strength of the ceramic bond diamond grinding wheel segment prepared in Comparative Example 4, the flexural strength of the Cu-MOF modified ceramic bond diamond grinding wheel segment of Example 4 is increased by 19.4%.

[0082] from Figure 3 and Figure 4 It can be seen that: Figure 3 After using conventional pore-forming agent (polymethyl methacrylate microspheres), nearly circular pores are formed in the grinding wheel block, which are relatively large in size with an average size of 50 μm. The basic ceramic binder has poor wetting and adhesion properties to diamond. Figure 4 The grinding wheel block after further introduction of Cu-MOF powder has formed pores that are closer to round, moderate in size, and evenly distributed. The average pore size is about 45μm, which is an ideal shape of pores with minimal impact on the strength of the binder. Not only can the pores play the role of chip holding, chip breaking, and storage of coolant with maximum efficiency, but the binder can also fully infiltrate the diamond particles, indicating that it has good bonding with diamond and strong holding ability, which helps to improve the performance and life of the grinding wheel block.

[0083] from Figure 5 and Figure 6It can be seen that: Figure 5 Middle a shows that with the conventional pore-forming agent (polymethyl methacrylate microspheres), nearly circular pores are formed in the grinding wheel block, which are relatively large in size with an average size of 55 μm; Figure 5 Figure b shows that the basic ceramic binder has poor wetting and adhesion properties on diamond. Figure 6 Figure a shows that after further introduction of Cu-MOF powder, the grinding wheel block forms a large number of pores with a size range of 8 to 45 μm and a high porosity, which helps to promote the pores to play the role of chip holding, chip breaking, and coolant storage with maximum efficiency; at the same time Figure 6 Figure b shows that the basic ceramic binder fully infiltrates the diamond, indicating that it has good bonding with the diamond and strong holding ability, which helps to improve the performance and life of the grinding wheel block.

[0084] from Figure 7 and Figure 8 It can be seen that: Figure 7 After using conventional pore-forming agent (polymethyl methacrylate microspheres), nearly circular pores are formed in the grinding wheel block. The pores are large in size with an average size of 50 μm, and the basic ceramic binder has poor wetting and adhesion properties to diamond. Figure 8 The grinding wheel block after further introducing Cu-MOF powder has an average pore size of about 30μm and a greatly increased porosity, which enables the pores to play the role of chip holding, chip breaking, and coolant storage with maximum efficiency. At the same time, the basic ceramic binder fully infiltrates the diamond, indicating that it has good bonding with diamond and strong holding ability, which helps to improve the performance and life of the grinding wheel block.

[0085] from Fig. 9 and Fig.10 It can be seen that: Fig. 9 After using conventional pore-forming agent (polymethyl methacrylate microspheres), irregular pores are formed in the grinding wheel block, with an average size of 50 μm. The basic ceramic binder has poor wetting and adhesion properties to diamond. Fig.10 The average pore size of the grinding wheel block after the introduction of Cu-MOF powder is about 50 μm, but compared with Fig. 9 The grinding wheel block has added a large number of micropores, the size of which is about 5 to 20 μm. The micropores can fully play the role of chip holding, chip breaking, and coolant storage. At the same time, the basic ceramic binder fully infiltrates the diamond, indicating that it has good bonding with diamond and strong holding ability, which helps to improve the performance and life of the grinding wheel block.

[0086] As can be seen from the above embodiments, the present invention provides a method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel block. First, silicon dioxide, boron trioxide, aluminum oxide and sodium oxide are mixed and then ground, smelted, quenched and dried in sequence to obtain a basic ceramic bond; isonicotinic acid and copper acetate monohydrate are mixed and ball milled to obtain Cu-MOF powder; finally, the basic ceramic bond, pore-forming agent, Cu-MOF powder, diamond particles and adhesive are mixed and then molded and sintered in sequence to obtain a Cu-MOF modified ceramic bond diamond grinding wheel block. The Cu-MOF powder in the present invention generates a large amount of gas during sintering, forming some small micropores distributed in the grinding wheel block. Copper atoms are oxidized into extremely fine copper oxide particles, which can strengthen the strength of the basic bond, thereby improving the performance of the grinding wheel.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Cu-MOF modified ceramic bond diamond grinding wheel segment, characterized in that: The steps include: (1) mixing silicon dioxide, boron trioxide, aluminum oxide and sodium oxide, grinding, smelting, rapid cooling and drying in sequence to obtain a basic ceramic binder; (2) mixing isonicotinic acid and copper acetate monohydrate and then ball milling to obtain Cu-MOF powder; (3) mixing a basic ceramic binder, a pore-forming agent, a Cu-MOF powder, diamond particles and an adhesive, and then sequentially performing a molding process and a sintering process to obtain a Cu-MOF-modified ceramic binder diamond grinding wheel block; In the step (3), the mass ratio of the basic ceramic binder, the pore former, the Cu-MOF powder, the diamond particles and the adhesive is 24-40:12-30:6-20:50-70:3-9; In the step (3), the sintering treatment includes a first stage sintering treatment and a second stage sintering treatment. The temperature of the first stage sintering treatment is 300-400°C, and the time of the first stage sintering treatment is 1-3 hours. The temperature of the second stage sintering treatment is 700-800°C, and the time of the second stage sintering treatment is 1-3 hours.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of silicon dioxide, boron trioxide, aluminum oxide and sodium oxide is 50-70:10-15:5-10:15-22.

3. The preparation method according to claim 2, characterized in that: In the step (1), the smelting temperature is 1200-1300° C. and the smelting time is 2-4 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (1), the drying temperature is 80 to 120° C. and the drying time is 6 to 12 hours.

5. The preparation method according to claim 4, characterized in that: In the step (2), the mass ratio of isonicotinic acid to cupric acetate monohydrate is 2 to 3:

1.

6. The preparation method according to claim 2, 3 or 5, characterized in that: In the step (2), the ball-to-material ratio of the ball milling treatment is 10 to 20:1, the rotation speed of the ball milling treatment is 500 to 600 rpm, and the ball milling treatment time is 2 to 4 hours.

7. The preparation method according to claim 6, characterized in that: The D50 of the diamond particles is 1-70 μm; and the pore-forming agent is polymethyl methacrylate microspheres.

8. The preparation method according to claim 5 or 7, characterized in that: In the step (3), the pressure of the molding process is 4 to 6 MPa, and the time of the molding process is 5 to 15 seconds.

Citation Information

Patent Citations

  • Preparation method for ceramic binder used for rapid synthesis of CBN abrasive tools by microwave method

    CN105084877A

  • Superhard accurate grinding wheel for machining polycrystalline diamond sheets and preparation method of superhard accurate grinding wheel

    CN117340798A

  • Diamond grinding head preparation method

    CN117484410A